Application of Hygiene and Sanitation Aspects in The Process of Handling of Animal Sacrifices During The Covid-19 Pandemic in Manokwari Regency - Edi Purwono; Elwin Elwin; Fathur Rohman Haryadi (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2022)
ABSTRACTHygiene is an effort conducted to obtain health. Hygiene is preventive actionthat focus on the object or activity of a human, whereas sanitization is defined as adisease preventive action that focuses on the environment around the object. Hygieneand sanitization are related to each other and cannot be separated to protect, maintainand increase the level of human health. The application of hygiene and sanitization Isneeded to maintain the quality of meat. The objective of this research is to determinethe application of hygiene and sanitization aspects to qurban handling activity in theManokwari District of West Papua. The method used in this research was the surveymethod which was conducted at 30 mosques in Manokwari District. The collected datawere then analyzed using a quantitative descriptive statistical method. The resultshowed that 66.67% of mosques that handled qurban have not applied hygiene andsanitization aspects to handling qurban whereas 33.33% of mosques have applied thehygiene and sanitization aspect. Based on the result can be concluded that mostmosques in Manokwari District have not applied hygiene and sanitization to the animalqurban handling process.